Agricultural Development-Marketing Nexus: Is Tengkulak truly Enemy of Smallholders in Indonesian Rural Area? - Muhammad Arsyad; Heliawaty Heliawaty; Yoshio Kawamura; Syarifuddin Yusuf (International Journal of Agriculture System, 2018)
This paper notes that a serious difficulty of smallholders in Indonesia is improving marketing networks of agricultural products. The marketing network in rural area is dominated by the brokers (called tengkulak). Smallholders do not have options to finance their production except for borrowing capital input from the tengkulak. Then the tengkulaks’ money will be repaid by smallholders in terms of agricultural products. It is true that smallholders get capital input, as well as daily life desires easily, on one hand. However, it also true that smallholders have no choice and they are ‘choked’ by the tengkulak in terms of price discrimination on the other hand. This phenomenon affects smallholder’s income. However, the tengkulak plays an important role in smallholder community. The first role is Financial/Capital Input provider. The tengkulak provides access to capital inputs for smallholders who are not able to get formal credit (banks). The second role is Production Process. The tengkulak facilitates smallholders in providing agricultural inputs. The third role is of Post-Production/ Marketing. The tengkulak enables smallholders to sell their agriculture products easily. The forth is Socio-religious role. Smallholders need money for schooling fees, medical care, donation for socio- religious activity by borrowing money from tengkulak without any administrative procedures. These facts above depicts that tengkulak is not truly enemy for smallholders.